2015
DOI: 10.1128/aac.05126-14
|View full text |Cite
|
Sign up to set email alerts
|

Photochemotherapeutic Strategy against Acanthamoeba Infections

Abstract: Acanthamoeba is a protist pathogen that can cause serious human infections, including blinding keratitis and a granulomatous amoebic encephalitis that almost always results in death. The current treatment for these infections includes a mixture of drugs, and even then, a recurrence can occur. Photochemotherapy has shown promise in the treatment of Acanthamoeba infections; however, the selective targeting of pathogenic Acanthamoeba has remained a major concern. The mannose-binding protein is an important adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…In addition [9], suggested photochemotherapeutic strategy against Acanthamoeba infections and showed that mannose-conjugated porphyrin has the potential for targeted photodynamic therapy of Acanthamoeba infections. Regardless of significant advances in Acanthamoeba keratitis treatment over the last decade or so, prevention still seems to be the best option.…”
Section: Treatmentmentioning
confidence: 99%
“…In addition [9], suggested photochemotherapeutic strategy against Acanthamoeba infections and showed that mannose-conjugated porphyrin has the potential for targeted photodynamic therapy of Acanthamoeba infections. Regardless of significant advances in Acanthamoeba keratitis treatment over the last decade or so, prevention still seems to be the best option.…”
Section: Treatmentmentioning
confidence: 99%
“…A keratitis isolate of A. castellanii belonging to the T4 genotype was purchased from the American Type Culture Collection (ATCC 50492). Amoebae were routinely grown in 10 ml PYG medium (0.75% [wt/vol] (13). The medium was changed 18 h before the experiment, and amoebae adherent to the flask, representing the trophozoite form, were collected by placing it on ice for 20 min with gentle agitation and used in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the morphology of nanoparticles, atomic force microscopic analysis was performed as described previously but with slight modifications (13). Briefly, a cover glass of 18-mm diameter was rinsed in distilled water, followed by three washes in 70% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the effects of these compounds are often amoebistatic, rather than amoebicidal (65); hence, prolonged clinical application is needed, which could result in the emergence of drugresistant strains, as seen in yeast such as Candida albicans, where azole resistance emerging through increased function of efflux mechanisms or through changes in the azole targets, e.g., C14 demethylase, or through changes in the biosynthetic steps of ergosterol synthesis has been observed. Similar mechanisms may explain variations in antimicrobial sensitivity among various isolates of Acanthamoeba (66). Overall, the ergosterol biosynthesis pathway is a potential target in the rational development of targeted therapeutic interventions against Acanthamoeba, as long as specificity is achieved to optimize the antiparasitic effects.…”
mentioning
confidence: 96%
“…Although rMBP is not applicable as a vaccine tool given the rarity of the disease, these findings have highlighted MBP as an important chemotherapeutic target. For example, recent studies showed that MBP-targeted chemotherapy can effectively eradicate amoebae in vitro and protect host cells against amoeba-mediated damage (66). Although studies are needed to prove the value of this approach in vivo, it has been suggested that mannose-conjugated porphyrin may have an application for targeted photodynamic chemotherapy against Acanthamoeba infections and should be explored for potential clinical applications in future investigations (66).…”
mentioning
confidence: 99%